Anaerobic Nitrogen Turnover by Sinking Diatom Aggregates at Varying Ambient Oxygen Levels - Stief, Peter; Kamp, Anja; Thamdrup, Bo; Glud, Ronnie N. (Frontiers in Microbiology, 2016)
In the world’s oceans, even relatively low oxygen (O2) levels inhibit anaerobic nitrogen cycling by free-living microbes. Sinking organic aggregates, however, might provide oxygen-depleted microbial hotspots in otherwise oxygenated surface waters. Here we show that sinking diatom aggregates can host anaerobic nitrogen cycling at ambient O2 levels well above the hypoxic threshold. Aggregates were produced from the ubiquitous diatom Skeletonema marinoi and the natural microbial community of seawater. Microsensor profiling through the center of sinking aggregates revealed internal anoxia at ambient 40% air saturation ( 100 µmol O2 L-1) and below. Accordingly, anaerobic nitrate turnover inside the aggregates was evident within this range of ambient O2 levels. In incubations with 15N-labeled nitrate, individual Skeletonema aggregates produced NO2- (up to 10.7 nmol N h-1 per aggregate), N2 (up to 7.1 nmol N h-1), NH4+ (up to 2.0 nmol N h-1), and N2O (up to 0.2 nmol N h-1). Intriguingly, nitrate stored inside the diatom cells served as an additional, internal nitrate source for N2 production, which may partially uncouple anaerobic nitrate turnover by diatom aggregates from direct ambient nitrate supply. Sinking diatom aggregates can contribute directly to fixed-nitrogen loss in low-oxygen environments in the ocean and vastly expand the ocean volume in which anaerobic nitrogen turnover is possible, despite relatively high ambient O2 levels. Depending on the extent of intracellular nitrate consumption during the sinking process, diatom aggregates may also be involved in the long-distance export of nitrate to the deep ocean.